Psychological Well-being of the Elderly in Yogyakarta City: Descriptive Study - Astuti, Budi; Rachmawati, Indriyana; Kurniasari, Mitta; Juwita Sari, Widya; Lestari, Rizqi (Kuras Institute, 2024)
Elderly people are a population that receives attention worldwide because when individuals enter the elderly period, life changes automatically occur, from productive to non-productive, even reduced physical abilities. This condition can undoubtedly affect the psychological well-being of the elderly because it requires them to adapt to new situations that have never been experienced before. This study aimed to determine the psychological well-being of the elderly through descriptive analysis and difference tests to find the results of differences in the psychological well-being of male and female elderly people. Three hundred twenty elderly people, both men and women, were involved in this study. These elderly people were selected using purposive sampling techniques in the Yogyakarta area. Data collection used a psychological well-being scale with six indicators, namely (1) self-acceptance, (2) life goals, (3) environmental mastery, (4) personal growth, (5) autonomy, and (6) positive relationships with others. The data that had been collected were then analyzed using descriptive statistics and the Wilcoxon test. The study results showed that the psychological well-being of male elderly people was 54.45, lower than that of female elderly people, who obtained a score of 54.51. In terms of age, the psychological well-being of elderly people was lower than that of elderly people. However, the overall results showed no difference in the psychological well-being of the male and female elderly with a p-value of 0,076>0,05. The psychological well-being of the elderly is better because it emphasizes the spiritual dimension in building a better meaning of life.